Psychometric analysis of the Utrecht Work Engagement Scale in the UWES-17S and UWES-9S versions in chilean university students - Jorquera Gutiérrez, Ricardo (2021)
Introduction: The UWES is one of the most widely used instruments in the world to measure academic engagement. Objective: The objective of this study was to describe and compare the psychometric properties of the UWES 17S and the UWES 9S in Chilean university students. Method: 541 students from a Chilean university participated, who voluntarily entered the indicated instruments. 61.6% of them were in the first year and 38.4% were at higher levels. Results: When comparing seven structural models, the best fit indicators were found in the UWES 9S according to a three-factor model and a bifactor model (X2/df=2.316; CFI=.977; TLI=.952; RMSEA=.071). The UWES 9S showed McDonald’s ω reliability indicators between .67 and .83 in its three factors, also demonstrating the invariance of its three-factor structure according to sex and at different levels of study. Discussion: It is concluded that the UWES 9S has adequate psychometric properties that would support its use to measure academic commitment in Chilean university students.